GAYA BELAJAR SISWA BERPRESTASI DALAM PEMBELAJARAN AQIDAH AKHLAK DI SMPIT BINA INSAN KAMIL DEPOK - Taufik; Sabilil Muttaqin; Sita Husnul Khotimah; Sayyidul Mubarok; Sarah Safira (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This study aims to determine the learning styles of outstanding students at SMPIT Bina Insan Kamil Depok, with a sample of 5 (five) outstanding students. Data collection was carried out through observation, interviews, questionnaires and documentation. Data analysis was carried out descriptively according to the data collected from the instrument. The results showed that each outstanding student had a different learning style, students A and B had an auditory learning style, students C and D had a visual learning style, and student E had a kinesthetic learning style